2020
DOI: 10.1186/s40985-020-00121-w
|View full text |Cite
|
Sign up to set email alerts
|

Involvement in maternal care by migrants and ethnic minorities: a narrative review

Abstract: Background: Guidelines for improving the quality of maternal health services emphasise women's involvement in care. However, evidence about migrant and ethnic minorities' preferences for participation in maternal care remains unsystematised. Understanding these populations' experiences with and preferred forms of involvement in care provision is crucial for imbuing policies and guidelines with sensitivity to diversity and for implementing people-centred care. This paper presents a narrative synthesis of empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 69 publications
(112 reference statements)
0
16
1
Order By: Relevance
“…Researchers even found that Somali women in the USA had substantial resistance to any labour-related intervention because they believed it would increase the risk of caesarean section or death 11. Other possible causes of disparities include difficulties accessing adequate information due to a language barrier, staff’s limited time, fewer opportunities offered to members of ethnic minorities to express personal preferences and prior suboptimal experiences with Western world healthcare institutions 12. An extensive literature review exploring women’s experiences of pregnancy confirmed that immigrant women often encountered difficulties navigating the healthcare system, being understood and receiving treatments respectful of their cultural background 13…”
Section: Introductionmentioning
confidence: 99%
“…Researchers even found that Somali women in the USA had substantial resistance to any labour-related intervention because they believed it would increase the risk of caesarean section or death 11. Other possible causes of disparities include difficulties accessing adequate information due to a language barrier, staff’s limited time, fewer opportunities offered to members of ethnic minorities to express personal preferences and prior suboptimal experiences with Western world healthcare institutions 12. An extensive literature review exploring women’s experiences of pregnancy confirmed that immigrant women often encountered difficulties navigating the healthcare system, being understood and receiving treatments respectful of their cultural background 13…”
Section: Introductionmentioning
confidence: 99%
“…Lower utilization of antenatal health care may be a consequence of barriers migrants face in accessing care, 22 including lack of social support, lack of health literacy, language barriers, lack of information, poor experience of care, and discrimination. 21,23 Furthermore, within the process of provision of healthcare services to migrant women, multiple factors associated with poor healthcare experiences have been previously documented, including difficulties related to communication, unfamiliarity with the healthcare system, lack of kind and respectful care, [24][25][26][27] lack of language support, cultural insensitivity, poor interactions with healthcare providers, lack of knowledge of legal entitlements and guidelines on the provision of welfare support and maternity care, 5,28 and outright discrimination. [27][28][29][30] The COVID-19 pandemic has, in addition to the increased burden on health systems, reshaped migration flows, the composition of migrant populations in Europe, and the economic panorama, with important consequences for migrants who are overrepresented in lowskilled professions.…”
Section: Introductionmentioning
confidence: 99%
“…Children from culturally and linguistically diverse backgrounds in English‐speaking countries, such as Australia, experience higher prevalence rates of overweight and obesity 11,12 . Families from culturally and linguistically diverse backgrounds may face challenges accessing early childhood interventions and services for various reasons, including language barriers and cultural differences 13–15 . To reduce overweight and obesity inequities, there is a pressing need to ensure early childhood interventions supporting healthy growth are culturally relevant and accessible to diverse populations.…”
Section: Introductionmentioning
confidence: 99%